Determinants of Female Labor Force Participation Rate in 2019-2023 in 34 Provinces of Indonesia - Avista Nur Aini; Muhammad Arif (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study examines the determinants of the Female Labor Force Participation Rate (FLFPR) across 34 provinces in Indonesia from 2019 to 2023, utilizing secondary panel data from the Indonesian Statistics Agency (BPS). Guided by relevant labor economics theories and prior empirical studies, this research considers key socioeconomic factors, including Female Labor Force Participation Rate (FLFPR), Average Years of Schooling (AYS), Life Expectancy of Women, Marital Status of Women, and Adjusted Per Capita Expenditure. Panel data regression analysis is conducted using the Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM), with model selection based on Chow and Hausman tests. Diagnostic tests are applied to address potential issues such as autocorrelation and heteroskedasticity, ensuring the robustness of results. Findings indicate that the FEM is the most suitable model, explaining 98.05% of the variation in FLFPR. Women's education, life expectancy, and per capita expenditure significantly influence FLFPR, while the marital status of women aged 20-24 does not show a significant impact. This unexpected result suggests the need for further exploration of regional and cultural differences in marriage and labor participation. Policy recommendations emphasize expanding educational access, improving healthcare services, and promoting women's economic independence. Future research should incorporate additional explanatory variables and alternative econometric approaches for a more comprehensive analysis.